To Study the Functional Outcome in Patients of Lateral Epicondylitis Treated with Platelet Rich Plasma - Mohd.Rizwan Khan; Nazim Mughal; Ajay Srivastav; Vinay Agarwal; Rav; Vidit (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Lateral epicondylitis, commonly known as tennis elbow, is characterized by inflammation of the common extensor tendon near the lateral epicondyle of the forearm, leading to persistent elbow pain. It affects approximately 1-3% of the population, particularly in individuals with occupations involving repetitive forearm movements such as construction, gardening, and computing. Traditionally treated with corticosteroid injections, new treatment options like platelet-rich plasma (PRP) have gained attention due to their regenerative properties, promoting tissue repair and healing. Objectives: This study aimed to evaluate the effectiveness of PRP injections in treating lateral epicondylitis by assessing pain reduction, wrist extensor strength, and functionality. Methodology: This randomized controlled trial was conducted at a tertiary care hospital over 12 months. A total of 50 participants with lateral epicondylitis were randomly assigned to receive either a PRP injection or a placebo saline injection. Participants were assessed at baseline, 4, 8, and 12 weeks post-treatment using DASH and VAS scores to measure pain and functionality. Data were analyzed using SPSS software with inferential statistics such as paired t-tests and ANOVA. Results: The study revealed a predominant age group of 31-40 years (44%) and a male majority (56%). Participants had a mean symptom duration of 5.2 ± 1.8 months. Baseline VAS and DASH scores indicated moderate to severe pain and disability. Post-treatment, significant reductions in pain (VAS) and disability (DASH) scores were observed, with VAS scores decreasing from 78.6 at baseline to 42.3, 24.7, and 18.2 at 4, 8, and 12 weeks, respectively (p < 0.001). Similarly, DASH scores improved from 64.3 to 45.2, 32.8, and 22.5 over the same period (p < 0.001). Pain relief was more pronounced in higher socioeconomic groups, with the upper and upper-middle classes showing significant improvement. Conclusion: PRP injections led to significant improvements in both pain and disability scores in patients with lateral epicondylitis, indicating their efficacy as a treatment option. The study also highlighted the role of socioeconomic status in treatment outcomes, with higher socioeconomic groups experiencing greater pain relief. Overall, PRP therapy demonstrates substantial benefits in managing lateral epicondylitis, providing a viable alternative to traditional treatments like corticosteroid injections.